Management of the clinically N0 neck in early-stage oral squamous cell carcinoma (OSCC). An EACMFS position paper. Issue 8 (August 2020) - Vassiliou, Leandros V.; Acero, Julio; Gulati, Aakshay; Hölzle, Frank; Hutchison, Iain L.; Prabhu, Satheesh; Testelin, Sylvie; Wolff, Klaus-Dietrich; Kalavrezos, Nicholas
Abstract: Metastasis of oral squamous cell carcinoma (OSCC) to the cervical lymph nodes has a significant impact on prognosis. Accurate staging of the neck is important in order to deliver appropriate treatment for locoregional control of the disease and for prognosis. The management of the neck in early, low volume disease (clinically T1 /T2 oral cavity tumours) has long been debated. The risk of occult nodal involvement in cT1 /T2 OSCC is estimated around 20–30%. We describe the natural evolutionary history of OSCC and its patterns of spread and metastasis to the local lymphatic basins. We discuss most published literature and studies on management of the clinically negative neck (cN0 ). Particular focus is given to prospective randomized trials comparing the outcomes of upfront elective neck dissection against the observational stance, and we summarize the results of the sentinel node biopsy studies. The paper discusses the significance of the primary tumour histological characteristics and specifically the tumour's depth of invasion (DOI) and its impact on predicting nodal metastasis. The DOI has been incorporated in the TNM staging highlighting its significance in aiding the treatment decision making and this is reflected in world-wide oncological guidelines. The critical analysis of all available literature amalgamates the existing evidence in early OSCC and provides recommendations in the management of the clinically N0 neck.